Three‐Dimensional Microscaffolds Exhibiting Spatially Resolved Surface Chemistry. (4th September 2013) - Richter, Benjamin; Pauloehrl, Thomas; Kaschke, Johannes; Fichtner, Dagmar; Fischer, Joachim; Greiner, Alexandra M.; Wedlich, Doris; Wegener, Martin; Delaittre, Guillaume; Barner‐Kowollik, Christopher; Bastmeyer, Martin
<x xml:space="preserve">Abstract</x> Spatial control over the surface chemistry of 3D organic–inorganic hybrid microscaffolds is achieved by a two‐photon‐triggered cycloaddition. Following a coating step with photoactivatable dienes via silanization, surface irradiation with a femtosecond‐pulsed laser in the presence of functional dienophiles enables a site‐selective alteration of the surface chemistry. Bioconjugation with fluorescent protein tags is employed to reveal the 3D molecular patterns. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>